Cog Is to Us as We Are to God: A Response to Anne Foerst - Gerhart, Mary (Zygon, 1998)
Foerst says that a robot must have human features if it is to learn to relate to human beings. She argues that the image of God (imago dei) represents no more than a promise of God to relate to us. In our view, however, the principle of embodied artificial intelligence (AI) in the robot suggests some kind of embodiedness of the image of God in human beings if they are to learn to relate to God. Foerst's description of how people react to a humanoid robot reads like Otto's description of the divine as mysterium fascinans et tremendum (awesome and alluring mystery). Her description makes robot-human interaction seem more religious than human-God interaction.